The Use of Digital Tools in Assessing Language and Literacy Development in Early Childhood Centres in Tamale Nanton District, Ghana - Abdul-Soaboor Ibrahim; Issah Mohammed (International Journal of Children, 2026)
The study investigated the use of digital tools in assessing language and literacy development in early childhood centres in the Tamale Nanton-district, Ghana. Specifically, the study examined the extent to which facilitators integrate digital tools in teaching practices, assessed facilitators’ levels of digital literacy skills, and explored the factors influencing the successful integration of digital tools in teaching. A total of 113 facilitators (39 males and 74 females) were selected from a population of 160 using simple random sampling. Data for this quantitative study were collected using a closed-ended questionnaire. The findings revealed that a significant majority of the facilitators did not use digital tools to assess learners' literacy and language development. Furthermore, the integration of digital tools in early childhood education in the district was found to be very low, with the availability of limited digital tools. The study recommends that the Nanton District Education Service strengthen monitoring and evaluation of facilitators’ teaching practices, while the Ministry of Education should organize periodic ICT workshops for early childhood facilitators. Additionally, the Ghana Education Service, in collaboration with the Tamale Nanton District, should provide adequate digital tools to schools.
Keywords: ICT integration; digital literacy; digital tools; early childhood education; language development; literacy development